Avaliação da capacidade física em trabalhadores: relação com o trabalho e o exercício físico - Barros, Fernanda Cabegi de (2020)
Musculoskeletal pain, among several factors, is related to the worker’s physical capacity. Adapting the physical work demands or increasing physical capacity, through the workplace-based exercise programme implementation, for example, are strategies for reducing musculoskeletal pain. Evidence for the association between physical capacity and occupational physical activities is still scarce. Despite the benefits of physical exercise, workers’ adherence, a factor identified as important for the effectiveness of physical exercise programs, is still little investigated. Thus, the objectives of this thesis were to investigate the association between occupational physical activity (AFO) measured objectively and the workers physical capacities (Study 1) and to evaluate the effects of adherence to a workplace-based exercise programme on physical capacity, pain intensity and productivity (Study 2).